A Slow or Modulatory Role of Astrocytes in Neurovascular Coupling. (April 2015) - Rosenegger, David George; Gordon, Grant Robert
Abstract Astrocytes are thought to play an important role in NVC, a process that allows the brain to locally control blood flow in response to changes in activity. However, there is an ongoing debate as to when, and under what conditions astrocyte activity is required. In the following review we set forth the hypotheses that astrocytes: (i) act to modulate but not initiate functional hyperemia and (ii) help set the basal tone state of the brain microvasculature by the tonic release of vaso‐active messengers. Through these actions astrocytes could help match metabolic demand with supply over a spectrum of activity timescales.